Methodological and reporting quality in laboratory studies of human eating behavior. (1st June 2018) - Robinson, Eric; Bevelander, Kirsten E.; Field, Matt; Jones, Andrew
Abstract: The methodological quality and reporting practices of laboratory studies of human eating behavior determine the validity and replicability of nutrition science. The aim of this research was to examine basic methodology and reporting practices in recent representative laboratory studies of human eating behavior. We examined laboratory studies of human eating behavior (N = 140 studies) published during 2016. Basic methodology (e.g., sample size, use of participant blinding) and reporting practices (e.g., information on participant characteristics) were assessed for each study. Some information relating to participant characteristics (e.g., age, gender) and study methodology (e.g., length of washout periods in within-subjects studies) were reported in the majority of studies. However, other aspects of study reporting, including participant eligibility criteria and how sample size was determined were frequently not reported. Studies often did not appear to standardize pre-test meal appetite or attempt to blind participants to study aims. The average sample size of studies was small (between-subjects design studies in particular) and the primary statistical analyses in a number of studies (24%) were reliant on very small sample sizes that would be likely to produce unreliable results. There are basic methodology and reporting practices in the laboratory study of human eating behavior that are sub-optimal and this is likely to be affecting the validity and replicability of research. Recommendations to address these issues are discussed.